2019
DOI: 10.1364/oe.27.024426
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically controllable random laser in ferromagnetic nematic liquid crystals

Abstract: This paper first reports random laser action in dye-doped ferromagnetic nematic liquid crystals, which act as a randomly distributed cavity. The random laser intensity of the ferromagnetic nematic liquid crystals can be controlled by a weak magnetic field (∼1 mT). Moreover, the magnetic switching of random laser is attributed to the direction and polarization dependent emission of light in the ferromagnetic nematic liquid crystals in an external magnetic field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…However, since the anisotropy of magnetic permeability of conventional LC materials is very low (~10 −6 ), a desired responsivity to the magnetic field is usually obtained by doping magnetic nanoparticles. Recent investigations have shown that doping with ferromagnetic nanoplatelets induces the formation of a ferromagnetic nematic LC phase [ 31 , 32 ], which enables LC reorientation with magnetic fields as low as a few mT [ 33 ]. Such LCs are very attractive for the construction of various kinds of magneto-optical device, among them also magnetically tunable DOEs.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the anisotropy of magnetic permeability of conventional LC materials is very low (~10 −6 ), a desired responsivity to the magnetic field is usually obtained by doping magnetic nanoparticles. Recent investigations have shown that doping with ferromagnetic nanoplatelets induces the formation of a ferromagnetic nematic LC phase [ 31 , 32 ], which enables LC reorientation with magnetic fields as low as a few mT [ 33 ]. Such LCs are very attractive for the construction of various kinds of magneto-optical device, among them also magnetically tunable DOEs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore several other scatterers include particles composed of zinc oxide, silica, TiO 2 -silica core-shell, alumina, tungsten oxide and nanoclays, ferromagnetic particles, polymeric fiber networks an even liquid crystals in ordered phases have been used to efficiently scatter light in colloidal RLs. Laser dyes, the most commonly used gain media are incorporated with nanomaterials scatterers such as ZnO, TiO 2 , WO 3 , biological tissues 48 , nematic liquid crystals 49,50,51,52,53,54,55 etc. When the dyes are injected into biologically active tissues, RL is generated in the system, which can be applied to separate cancerous and normal tissues 56,48 .…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…Laser dyes, the most commonly used gain media, are incorporated with nanomaterials scatterers such as ZnO, TiO 2 , WO 3 , biological tissues, 48 nematic liquid crystals [49][50][51][52][53][54][55] etc. When the dyes are injected into biologically active tissues, RL is generated in the system, which can be applied to separate cancerous and normal tissues.…”
Section: General Considerations and Examples For Active Platforms Of Rlmentioning
confidence: 99%
See 1 more Smart Citation
“…[159][160][161][162] To further control the lasing properties, magnetically controllable Fe 3 O 4 nanoparticles were employed to develop controllable RLs. [163,164] Particularly, metal nanoparticles were used as scatterers for enhancing the lasing performance of RLs thanks to its larger scattering cross-section and the localized surface plasmon resonance (LSPR) enhanced electromagnetic field. Based on plasmonic scattering, Shi et al achieved a low-cost RLs by using self-assembled Ag nanoparticles and polymer film coated on the fiber facet, demonstrating the detection of RI and IgG.…”
Section: Optical Resonance Based On Random Scatteringmentioning
confidence: 99%